PLANT-BASED REMEDIES FOR THE MANAGEMENT OF DIABETES - Gupta, Sumiksha; Sidhu, M.C.; Ahluwalia, A.S. (Current Botany, 2017)
The knowledge related to medicinal plants have been described in Indian Ayurveda System and survived till today through the prevalent socio-cultural practices. Present study is an attempt to document anti-diabetic plants from Una district of Himachal Pradesh. A thorough survey was conducted from 500 respondents using a semi-structured questionnaire and informal discussions. A total of 84 anti-diabetic plant species have been recorded. These plants include wild (32) or cultivated (41) species. Fabaceae was the dominant family with 10 species. The phytoremedies were prepared using different plant parts or sometimes even the whole plant or in combination with other species. There are only few reports on anti-diabetic use of some wild species from the study area. Further studies of bioactive compounds in these species can depict their hypoglycemic potential. Present study has suggested a strong link between traditional herbal medicines, their documentation and proper chemical characterization to harness their therapeutic potential to the maximum.Â Â  KEY WORDS: Diabetes, bioactive compounds, traditional medicines, phytoremedies, angiosperms, Una, Himachal Pradesh